2009
DOI: 10.1103/physrevb.79.014436
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization reversal in circularly exchange-biased ferromagnetic disks

Abstract: We investigate the reversal behavior of circularly exchange-biased micron-sized bilayer disks of Permalloy ͑Py͒/IrMn and CoFe/IrMn. A circular exchange bias is induced by imprinting the vortex configuration of the ferromagnetic layer into the IrMn when the disks are cooled in zero external field through the blocking temperature of IrMn. The resulting circular exchange bias has a profound effect on the reversal behavior of the ferromagnetic magnetization. In Py/IrMn disks the reversal takes place via vortex mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…This configuration is equivalent to what is obtained experimentally by a ZFC process, as was reported in Refs. [16][17][18][19]. As a validation test, we have also done simulations with the exchange bias defined as a fixed circular field, and the results were equivalent to the results obtained in the case of a fixed spin layer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This configuration is equivalent to what is obtained experimentally by a ZFC process, as was reported in Refs. [16][17][18][19]. As a validation test, we have also done simulations with the exchange bias defined as a fixed circular field, and the results were equivalent to the results obtained in the case of a fixed spin layer.…”
Section: Resultsmentioning
confidence: 99%
“…The larger observed values of nucleation and annihilation fields for exchange-biased vortex are in agreement with results reported in literature. [17][18][19] It was suggested that the increase in both nucleation and annihilation fields must be equal to the exchange field. 16,21 On the other hand, Sort et al 21 observed that simulation results differ to experimental data by presenting slightly larger annihilation fields, which is in accordance with our results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, magnetization reversal in exchange biased permalloy (Py)/IrMn disks of 1 lm diameter was investigated. [4][5][6][7][8][9] The magnetization reversal in such structures is found to be dependent on the applied field direction. If the applied in-plane field is along the exchange bias direction, the magnetization reverses via nucleation and annihilation of the vortex.…”
mentioning
confidence: 95%
“…The magnetostatic problem is ubiquitous for any system that involves patterned micronor sub-micron size magnetic bodies, such as read or write heads in magnetic hard disk drives, magnetic nanoparticles 25 , coupled magnetic disks 26,27 , or artificial spin ices 28 . In patterned ferromagnetic systems, there typically arises a competition between the short-range exchange interactions and long-range magnetostatic interactions.…”
Section: B Magnetostatic Problemmentioning
confidence: 99%